-g+2(3+g)=-4(g-4)

Simple and best practice solution for -g+2(3+g)=-4(g-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -g+2(3+g)=-4(g-4) equation:


Simplifying
-1g + 2(3 + g) = -4(g + -4)
-1g + (3 * 2 + g * 2) = -4(g + -4)
-1g + (6 + 2g) = -4(g + -4)

Reorder the terms:
6 + -1g + 2g = -4(g + -4)

Combine like terms: -1g + 2g = 1g
6 + 1g = -4(g + -4)

Reorder the terms:
6 + 1g = -4(-4 + g)
6 + 1g = (-4 * -4 + g * -4)
6 + 1g = (16 + -4g)

Solving
6 + 1g = 16 + -4g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '4g' to each side of the equation.
6 + 1g + 4g = 16 + -4g + 4g

Combine like terms: 1g + 4g = 5g
6 + 5g = 16 + -4g + 4g

Combine like terms: -4g + 4g = 0
6 + 5g = 16 + 0
6 + 5g = 16

Add '-6' to each side of the equation.
6 + -6 + 5g = 16 + -6

Combine like terms: 6 + -6 = 0
0 + 5g = 16 + -6
5g = 16 + -6

Combine like terms: 16 + -6 = 10
5g = 10

Divide each side by '5'.
g = 2

Simplifying
g = 2

See similar equations:

| 2[w-(2w+10)+8]=2(w+2) | | 5(y-2)=6(y-1) | | 3(2k+18)=6(9+k) | | 4x^2+56x+156=0 | | s=4s-60 | | 9x-20=7x+16 | | 140=(2x-2)(2x+2) | | 6(5-5y)= | | t^3+t=4930 | | 2z/2= | | 11+x+24=19+x+22 | | 0.75(4x+8)=-3 | | 5k-15+j=3j-5 | | 3(2g+7m)= | | (x+x)-20x+100=0 | | 0.2r=-8 | | v+53=3v+21 | | 9=5.4*x | | 5y^2+7y-4=0 | | 12-4p=-4(-5p-3) | | (5x-15)=what | | 5y-2=3x+2 | | 4(-2f-6g)= | | 3x=2.52 | | 140=4x^2-4+4-16 | | x^1000=0.9 | | 3y=-x+0 | | 13w+16w-7+5=-5w+5-7 | | 4x^2-156=0 | | 8(-4k-4)=-5k-32 | | 3(3+2j)= | | 3z-35=5z-87 |

Equations solver categories